Effectiveness of the influenza vaccine for preventing laboratory-confirmed influenza infections in outpatient immunocompromised adults, 2017-2018 - Kailey Hughes Kramer; Richard K. Zimmerman; Catherine L. Haggerty; G. K. Balasubramani; Mary Patricia Nowalk; Emily T. Martin; Manjusha Gaglani; C. Hallie Phillips; Edward Belongia; Jessie Chung; Fernanda P. Silveira (Taylor & Francis Group, 2024)
While the number of immunocompromised (IC) individuals continues to rise, the existing literature on influenza vaccine effectiveness (VE) in IC populations is limited. Understanding the vaccine effectiveness (VE) of the seasonal influenza vaccines in immunocompromised (IC) populations remains paramount. Using 2017-2018 US Flu VE Network data, we examined the VE of the 2017-2018 seasonal influenza vaccine against symptomatic influenza in outpatient settings among IC adults. We used logistic regression and adjusted for enrollment site, race, self-reported general health status, age, and onset date of symptoms. The VE among non-IC was 31% (95% CI: 22, 39) and among IC participants was −4% (95% CI: −66, 35), though the difference was not statistically significant. This study demonstrates the capacity to study a large IC population using an existing influenza VE network and contributes to the literature to support large, multicenter VE studies for IC populations.